Publisher Correction: The default network of the human brain is associated with perceived social isolation (Nature Communications, (2020), 11, 1, (6393), 10.1038/s41467-020-20039-w) - Spreng, R. Nathan (Nature Research, 2022)
10.1038/s41467-021-23623-w